2023
DOI: 10.1080/19490976.2023.2201160
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics to improve the gut microbiome in premature infants: are we there yet?

Abstract: Gut microbiome maturation in infants born prematurely is uniquely influenced by the physiological, clinical, and environmental factors surrounding preterm birth and early life, leading to altered patterns of microbial succession relative to term infants during the first months of life. These differences in microbiome composition are implicated in acute clinical conditions that disproportionately affect preterm infants, including necrotizing enterocolitis (NEC) and late-onset sepsis (LOS). Probiotic supplementa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 172 publications
0
7
0
1
Order By: Relevance
“…These bacteria play a role in competitive adhesion, disruption of the information transmission of harmful microorganisms, and maintenance of the intestinal microecology through their metabolites [27,28]. Furthermore, Lactobacillus can directly access the intestinal epithelium and participate in the cell surface factors recognition that modulates epithelial cell anti-inflammatory and anti-apoptotic functions and maintains intestinal epithelial cell viability [29][30][31]. Moreover, Lactobacillus can regulate intestinal microecology by controlling specific functions of the mucosal immune system through the mucosal immune system or epithelial cells [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…These bacteria play a role in competitive adhesion, disruption of the information transmission of harmful microorganisms, and maintenance of the intestinal microecology through their metabolites [27,28]. Furthermore, Lactobacillus can directly access the intestinal epithelium and participate in the cell surface factors recognition that modulates epithelial cell anti-inflammatory and anti-apoptotic functions and maintains intestinal epithelial cell viability [29][30][31]. Moreover, Lactobacillus can regulate intestinal microecology by controlling specific functions of the mucosal immune system through the mucosal immune system or epithelial cells [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…A recently published review highlights that infants treated with probiotics have bountiful Bifidobacterium spp. independent of the probiotic formulation and reduction in potentially pathogenic bacteria [ 94 ]. Probiotics containing both Bifidobacterium and Lactobacillaceae can influence the preterm gut microbiome configuration while promoting the development of a microbiome that is more typical of term newborns [ 95 ].…”
Section: Stress and Gut Microbiota Brain Axismentioning
confidence: 99%
“…Previous studies have revealed the association between Bifidobacterium deficiency and the higher incidence of intestinal disorders . A study showed that administration of Bifidobacterium reduced the risk of NEC in preterm infants . Thus, Bifidobacterium may have a positive influence on intestinal maturation in the early stages of life.…”
Section: Introductionmentioning
confidence: 99%
“…15 A study showed that administration of Bifidobacterium reduced the risk of NEC in preterm infants. 16 Thus, Bifidobacterium may have a positive influence on intestinal maturation in the early stages of life.…”
Section: ■ Introductionmentioning
confidence: 99%